A review of the application of the high nature value concept in Estonia within the context of the European Union. (2015) - Kikas, Tambet; Bunce, Robert Gerald Henry; Kull, Ain; Sepp, Kalev
Since the 1990s, the concept of High Nature Value (HNV) farmland has been accepted in Europe as a landscape measure that is correlated with biodiversity. Farmland is land used for agriculture and includes fields, linear features, woodlands, and grazed forests. The objective of the paper is to provide an introduction to the concept in Estonia, in order to identify relevant parameters. The paper firstly summarises the background and history of HNV, which is designed as a policy tool to support low intensity farming. In Estonia a map of potential HNV is now being developed, based on relevant national information, because of limitations in European databases. These problems are illustrated by an analysis of the situation in Estonia, with the conclusion that detailed national data will improve the accuracy of the map, which can then be used for policy formulation for conservation of biodiversity in the country.